Design and Implementation of a Weather Monitoring System Base on IoT Blynk Display and Solar Panel : Perancangan dan Implementasi Sistem Pemantauan Cuaca Berbasis IoT dengan Tampilan Blynk dan Panel Surya - Widayanti; Fajarrohman, Ashadi (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2024)
In order to support precision agriculture, this project intends to design, develop, and test a weather monitoring system based on the ESP32 microcontroller coupled with solar panel and an Internet of Things (IoT) -based display via Blynk. Blender was used to model the system, while Fritzing was used to produce the circuit diagrams. It uses the appropriate sensors to measure temperature, humidity, rainfall, and wind speed. Performance testing revealed repeatability precision values of 98,97%, 89,22%, 95,27%, and 9,19%, respectively, and accuracy levels of 99,76% (temperature), 99,48% (humidity), 98,41% (rainfall), and 89,83% (wind speed). The findings show limitations in the accuracy of wind speed measurement but show good performance for the majority of metrics. Weather-based agricultural decision-making can be improved by this method, especially in isolated locations without adequate monitoring infrastructure.